Cost-effectiveness of polatuzumab vedotin plus chemoimmunotherapy for untreated diffuse large B-cell lymphoma in China - Mengya Li; Qian Li; Yinhui Zhang; Changjing Xu; Zhu Chen; Yilan Huang; Longyang Jiang (Scientific Reports)
Abstract In recent years, antibody-drug conjugates have become clinically significant in oncology therapeutics. Results from the POLARIX trial revealed that polatuzumab vedotin in combination with rituximab, cyclophosphamide, doxorubicin, and prednisone (Pola-R-CHP) versus rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) reported a 7.7% improvement in the 3-year progression-free survival (PFS), with no difference in overall survival (OS). This study aimed to assess the cost-effectiveness of polatuzumab vedotin in the first-line treatment of diffuse large B-cell lymphoma (DLBCL) from the perspective of the Chinese healthcare system. We constructed a 3-state partitioned survival model and a 10-year horizon to estimate the cost and utility associated with DLBCL treatment. The survival data, direct medical costs, and utilities were obtained from the POLARIX trial, YAOZHI database, and published literature. The outputs of the model include total costs, quality-adjusted life-years (QALYs), and incremental cost-effectiveness ratios (ICERs). Uncertainty was explored through one-way, probabilistic sensitivity and scenario analyses. Over a 10-year horizon, Pola-R-CHP provided an additional 0.29 QALYs versus R-CHOP, while incurring incremental costs of $31,804 and an ICER of $110,594/QALY. One-way sensitivity analysis suggested that the model was most sensitive to the utility of PFS and the cost of polatuzumab vedotin. Probabilistic sensitivity analysis showed that at the willingness-to-pay (WTP) threshold ($38,043), Pola-R-CHP was not considered cost-effective. Scenario analyses indicated that Pola-R-CHP could be a cost-effective therapeutic alternative for patients achieving long-term survival. The threshold analysis demonstrated that a 61% price reduction for polatuzumab vedotin would achieve cost-effectiveness at the WTP threshold. In the first-line treatment of DLBCL, Pola-R-CHP provides an additional health benefit over R-CHOP, but is unlikely to be cost-effective at currently published prices.